2011
DOI: 10.1002/cctc.201100016
|View full text |Cite
|
Sign up to set email alerts
|

Anion–Cation Cooperative Catalysis by Ionic Liquids

Abstract: The cooperative effects of cation–anion are elucidated in ionic liquid‐catalyzed reactions of aniline with ethylene carbonate and the reaction of phenylacetonitrile with dimethyl carbonate. Cations of ionic liquids activate electrophiles by the proton in the 2‐position of the imidazolium ring through the hydrogen‐bond interaction with the carbonyl group. The catalytic activity follows the order of 1‐butyl‐3‐methyl‐imidazolium ([Bmim])>1,2‐dimethyl‐3‐butyl imidazolium ([Bmmim])>1‐butyl‐pyridinium ([Bpy]), which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 82 publications
(51 citation statements)
references
References 47 publications
3
48
0
Order By: Relevance
“…Gao's group recently reported 122,123 an alternative strategy for the selective preparation of 3-substituted cyclic carbamates from the reaction between a cyclic carbonate (made using CO 2 ) and aromatic amines using 1-butyl-3-methylimidazolium acetate (BmimOAc) as catalyst (Scheme 14). DFT calculations revealed that both the cationic and the anionic moieties of the catalyst activate in a cooperative fashion the substrates (i.e., cyclic carbonates and aromatic amines) by means of hydrogen-bonding.…”
Section: 119-121mentioning
confidence: 99%
“…Gao's group recently reported 122,123 an alternative strategy for the selective preparation of 3-substituted cyclic carbamates from the reaction between a cyclic carbonate (made using CO 2 ) and aromatic amines using 1-butyl-3-methylimidazolium acetate (BmimOAc) as catalyst (Scheme 14). DFT calculations revealed that both the cationic and the anionic moieties of the catalyst activate in a cooperative fashion the substrates (i.e., cyclic carbonates and aromatic amines) by means of hydrogen-bonding.…”
Section: 119-121mentioning
confidence: 99%
“…Task‐specific supported IL‐like phases modified with sulfonic groups ( 9 a , Figure ) can be used to complex lanthanide triflates, in particular scandium triflate [Sc(OTf) 3 ] . In this regard, the presence of the imidazolium fragments in 9 a can contribute to the improvement of the catalytic activity provided by the Lewis‐acid units . Such contribution is absent in the analogous Sc‐supported catalyst 9 b , prepared from a commercially available sulfonic polystyrene‐divinylbenzene polymer (Amberlyst 15) …”
Section: Resultsmentioning
confidence: 98%
“…The conversion of CO 2 to cyclic carbonates via epoxide substrates is a 100 % atom economic reaction, and the products are of wide applicability as electrolytes of Li ion batteries, aprotic solvents, degreasing agents, monomers for polymer synthesis, etc. [26][27][28][29].…”
Section: Introductionmentioning
confidence: 98%